Histamine and Th2 cytokines independently and synergistically upregulate MMP12 expression in human M2 macrophages - Pereira da Fonseca, Alice; Traidl, Stephan; Gutzmer, Ralf; Schaper-Gerhardt, Katrin; Werfel, Thomas; Mommert, Susanne (Frontiers in Immunology, 2024)
Beyond Th2 cells and various immune cells, M2 macrophages have been identified in lesional skin of atopic dermatitis (AD) indicating their involvement in the disease’s underlying mechanisms. MMP12, a matrix-degrading enzyme, which is predominantly produced by macrophages, is increased in skin lesions of AD patients. In this study we investigated the expression of MMP12 mRNA in lesional AD skin at single cell level through RNA sequencing (scRNA-seq) and the expression of MMP12 in M2 macrophages from healthy individuals and AD patients in response to Th2 cytokines and histamine using quantitative PCR and ELISA. Additionally, we analyzed macrophages from dupilumab-treated AD patients using the same methods to assess the influence of Th2 cytokines on MMP12 expression ex-vivo. ScRNA-seq identified macrophages as the primary producers of MMP12 in lesional AD skin. In-vitro, both MMP12 mRNA and protein expression were significantly increased in monocytes during differentiation to M2 macrophages in the presence of histamine, of Th2 cytokines or of Th2 cytokines in combination with histamine. In M2 macrophages obtained from dupilumab-treated AD patients, the upregulation of MMP12 expression by IL-4 and IL-13 was attenuated. Our findings unveil a novel mechanism whereby Th2 cytokines and histamine regulate MMP12 expression, potentially impacting skin barrier homeostasis in AD.